MODELLING AND SIMULATION OF UNRELIABLE M/M/n/n QUEUEING SYSTEM (Perner's Contacts, 2010)
This paper is devoted to modelling and simulation of a Markov multi-server queueing system subject to breakdowns and with an ample repair capacity, the system do not form the queue of waiting customers. The paper introduces a mathematical model of the studied system and a simulation model created by using software CPN Tools. At the end of the paper the outcomes which were reached by both approaches will be shown and statistically evaluated.
Keywords: M/M/n/n; Queueing system; Breakdown; Petri net